2012
DOI: 10.1007/s00216-012-6293-z
|View full text |Cite
|
Sign up to set email alerts
|

An innovative, easily fabricated, silver nanoparticle-based titanium implant coating: development and analytical characterization

Abstract: Microbial colonization and biofilm formation on implanted devices represent an important complication in orthopaedic and dental surgery and may result in implant failure. Controlled release of antibacterial agents directly at the implant site may represent an effective approach to treat these chronic complications. Resistance to conventional antibiotics by pathogenic bacteria has emerged in recent years as a major problem of public health. In order to overcome this problem, non-conventional antimicrobial agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 59 publications
1
62
0
2
Order By: Relevance
“…10,11 Ag NPs have promising antibacterial activity but the small size and high mobility raise safety concerns due to their potential cytotoxicity. 26 In this study, size tunable Ag NPs were fabricated and incorporated onto SLA surfaces by manipulating the ASH effect of Ag-PIII. It was found that immobilization of Ag NPs on SLA-treated titanium gave rise to both good antibacterial activity and excellent compatibility with mammalian cells (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Ag NPs have promising antibacterial activity but the small size and high mobility raise safety concerns due to their potential cytotoxicity. 26 In this study, size tunable Ag NPs were fabricated and incorporated onto SLA surfaces by manipulating the ASH effect of Ag-PIII. It was found that immobilization of Ag NPs on SLA-treated titanium gave rise to both good antibacterial activity and excellent compatibility with mammalian cells (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…25 For instance, Zhao et al 25 and De Giglio et al 26 have reported that coatings incorporating Ag NPs exhibit some cytotoxicity toward osteoblasts, which is probably due to the silver ions (Ag + ) released by Ag NPs. 27 Hence, restricting the mobility of Ag NPs by immobilization is crucial in reducing the toxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…It must be considered that not only Ag þ ions but also silver nanoparticles migrate through the PPX cap layer. 31 Silver nanoparticles can interact with biological fluids as metallic particles (Ag 0 ) or can be oxidized to Ag þ . 20 However, ICP-OES cannot discriminate between these two species; therefore, release of both species by measuring the sample solutions by this method cannot be excluded.…”
Section: G Silver Ion Release From Hydrophilic Ag/ppx-n In Syntheticmentioning
confidence: 99%
“…13 While many treatments can create similar roughness measurements, such as adding coatings onto the surface via electrophoretic deposition, 2 electrochemical anodizing [14][15][16] and silver nanoparticle-embedded hydrogelbased coatings, 17 the morphology of the resulting surfaces can vary drastically. Lorenzetti et al 11 used hydrothermal treatments to generate nanorough surfaces on titanium and found that macro-and microscale grooves (results of the initial material machining process) provided niches for bacteria to adhere and proliferate on, despite high roughness values.…”
Section: Introductionmentioning
confidence: 99%
“…Lorenzetti et al 11 used hydrothermal treatments to generate nanorough surfaces on titanium and found that macro-and microscale grooves (results of the initial material machining process) provided niches for bacteria to adhere and proliferate on, despite high roughness values. Silver is one of the most prominent non-small-molecule drugs used for antibacterial applications, 3,[17][18][19] but can be expensive and mildly toxic to surrounding mammalian cells. 20,21 Additionally, adding different materials to the surface may lead to imperfectly fused layers that may eventually wear or delaminate from the bulk implant.…”
Section: Introductionmentioning
confidence: 99%